2020
DOI: 10.1111/cen.14347
|View full text |Cite
|
Sign up to set email alerts
|

The progression of salt‐wasting and the body weight change during the first 2 weeks of life in classical 21‐hydroxylase deficiency patients

Abstract: BackgroundOne of the major purposes of newborn screening for 21‐hydroxylase deficiency (21OHD) is preventing life‐threatening adrenal crisis. However, the details of adrenal crisis in newborns are not precisely documented.AimWe aimed to clarify the clinical details of salt‐wasting in newborn 21OHD patients.MethodsBased on the follow‐up survey of the screening in Tokyo from 1989 to 2017, we retrospectively analysed the conditions of classical 21OHD neonates before the initiation of therapy.ResultsOne hundred cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 32 publications
1
21
0
Order By: Relevance
“…Neonates with 17αOHP levels more than the retest cutoff value are retested. When the 17αOHP levels are higher than the retest cutoff value two-three times, the screening is considered positive (Figure 2) [4,5,[11][12][13]. In some female patients, blood sampling for the screening is performed ahead of schedule due to atypical genitalia, which is one of the major clinical symptoms in female neonates with 21OHD and is frequently recognized at birth.…”
Section: Screening System In Japanmentioning
confidence: 99%
See 3 more Smart Citations
“…Neonates with 17αOHP levels more than the retest cutoff value are retested. When the 17αOHP levels are higher than the retest cutoff value two-three times, the screening is considered positive (Figure 2) [4,5,[11][12][13]. In some female patients, blood sampling for the screening is performed ahead of schedule due to atypical genitalia, which is one of the major clinical symptoms in female neonates with 21OHD and is frequently recognized at birth.…”
Section: Screening System In Japanmentioning
confidence: 99%
“…Furthermore, even in cases of 21OHD, the possibility of developing severe salt wasting, such as hyponatremia (<130 mEq/L) or hyperkalemia (>7 mEq/L), is extremely low without loss of body weight (Figure 4). Contrary to body weight change, the relevance of predicting severe salt wasting based on the 17αOHP level is extremely low because the 17αOHP level is not associated with Na or K levels [13]. Although the findings of body weight change in patients cannot be the direct criteria for the CAH screening protocol, they may assist in some individual cases, e.g., for triaging Although the findings of body weight change in patients cannot be the direct criteria for the CAH screening protocol, they may assist in some individual cases, e.g., for triaging a neonate with a positive result who is living in a region with limited access to a pediatric endocrinologist or in which there is no CAH screening.…”
Section: Triage Of the Neonates With Salt Wasting By Body Weight Changementioning
confidence: 99%
See 2 more Smart Citations
“…Such crises typically occur in the second or third week of life, sometimes prior to the reporting of screening results. Rapid collection, transport, and processing of specimens and rapid reporting of markedly abnormal results can allow for early onset of treatment prior to the emergence of severe symptoms and can reduce the need for, or length of, neonatal hospitalizations [ 36 ]. In one pilot screening study, six unscreened males with SW-CAH were all hospitalized with adrenal or SW crises, compared with none of five screened males with SW-CAH [ 37 ]; another study found 0/17 and 10/40 frequencies of hospitalization in screened and unscreened infants with CAH [ 17 ].…”
Section: Introductionmentioning
confidence: 99%